If it's not what You are looking for type in the equation solver your own equation and let us solve it.
22-3x=x+6
We move all terms to the left:
22-3x-(x+6)=0
We get rid of parentheses
-3x-x-6+22=0
We add all the numbers together, and all the variables
-4x+16=0
We move all terms containing x to the left, all other terms to the right
-4x=-16
x=-16/-4
x=+4
| 18+7-x=12-112 | | 900x=1800 | | 101+58+58=x | | 9.t=81 | | 101-58=x | | 99/9*2=27x | | 9k+21=-33 | | 101+58=x | | (4x+16)+(7x-1)=180 | | 4x+3=15–2x | | 3r+2–r=-4 | | (0.5)^3x+2=8^(5x-4) | | –8−3n=10−5n | | (2x-39)°(3x+14)= | | 2x+12=88 | | x^2+23=123 | | 2f+13=-11 | | 130+40=y | | x/5+x+1/3=2 | | –5c=–8c+9 | | 7x-13=4x= | | 7-20x*4=-128+27 | | h-(-13.94)=21.06 | | 36+63=y | | 3.6d=2.7 | | 25-6a=7 | | x+18.99=14 | | 34-y/2=-12 | | 2y–12=22 | | 3x+28=5x-16 | | .4=32b | | 3-y=63−y=6 |